Interpenetrating polymeric network hydrogel for stomach-specific drug delivery of clarithromycin: Preparation and evaluation (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this study was to develop a controlled release system targeting antibiotic delivery to the stomach. The hydrogels were synthesized by using chitosan, poly (acrylic acid) and poly (vinyl pyrrolidone) polymers crosslinkedwith glutaraldehyde and N,N’-methylenebisacrylamide. Interpenetrating polymeric network (IPN) hydrogels were prepared by varying the concentration of crosslinking agent (glutaraldehyde). The amount of chitosan, poly (acrylic acid), poly (vinyl pyrrolidone) and N,N’-methylenebisacrylamide were kept constant in all formulations. The effect of glutaraldehyde concentration on the swelling and release characteristics were evaluated. Modalities used to assess the most optimal hydrogel formulation included high liquid chromatography, FTIR analysis, differential scanning calorimetry, swelling studies, in vitro drug release study, mucoadhesive study and scanning electron microscopy. The result showed that IPN hydrogels were greater in swelling, more mucoadhesive and released more drug at lower pH values. Thus, it is believed that the antibioticconcentration in the stomach might be sustained through this formulation.